High-pressure hydrogen sulfide by diffusion quantum Monte Carlo - Azadi, Sam; Kühne, Thomas D. (Journal of Chemical Physics, 2017)
We revisit the enthalpy-pressure phase diagram of the various products from the different proposed decompositions of H2S at pressures above 150 GPa by means of accurate diffusion Monte Carlo simulations. Our results entail a revision of the ground-state enthalpy-pressure phase diagram. Specifically, we find that the C2/c HS2 structure is persistent up to 440 GPa before undergoing a phase transition into the C2/m phase. Contrary to density functional theory, our calculations suggest that the C2/m phase of HS is more stable than the I41/amd HS structure over the whole pressure range from 150 to 400 GPa. More importantly, we predict that the Im-3m phase is the most likely candidate for H3S, which is consistent with recent experimental x-ray diffraction measurements.
CRIS-Team Scopus Importer:2023-03-20